A Comparative Study of Angoff’s and Nedelsky’s Models to Determine the Cut-off Score for a Criterion-Referenced Test in Mathematics - Shreim, Ahmad; Swalmeh, Yousef (Jordan Journal of Educational Sciences, 2006)
This study aimed at comparing Angoff’s and Nedelsky’s models to determine the cut-off score for a criterion-referenced test in mathematics with and without item difficulty indices. The test consisted of 30 multiple-choice items,with four alternatives for each. The sample consisted of 80) male and female raters. The raters were distributed randomly into four equal separate groups. The results of the study indicated that the cut-off score ranged from 0.62 to 0.68 using Angoff’s model and from 0.49 to 0.57 using Nedelsky’s model. Furthermore, the differences between the reliability coefficients of Angoff’s and Nedelsky’s models with or without the raters’ knowledge of the values of the item difficulty coefficients were not statistically significant at (α = 0.05).